Evaluation of Medication Adherence and Pharmacokinetics of Dasatinib for Earlier Molecular Response in Japanese Patients With Newly Diagnosed Chronic Myeloid Leukemia: A Pilot Study. Issue 5 (October 2019) - Iwamoto, Takuya; Monma, Fumihiko; Ohishi, Kohshi; Umino, Akira; Suzuki, Kei; Oka, Koji; Kawakami, Keiki; Sekine, Takao; Okuda, Masahiro; Katayama, Naoyuki
Abstract : Background: Tyrosine kinase inhibitors markedly improve the survival for patients with chronic myeloid leukemia (CML). However, a decrease in adherence leads to undesired therapeutic outcomes. In this study, the relationships among adherence, pharmacokinetics, response, and adverse effects for dasatinib treatment were prospectively investigated. Methods: This study was a prospective cohort study of patients with newly diagnosed CML at 4 general hospitals and 1 university hospital. Patients started to receive dasatinib 100 mg once daily. A Medication Event Monitoring System was used to assess medication adherence and the medication possession ratio during the 12 months. Plasma concentrations of dasatinib were measured using liquid chromatograph-tandem mass spectrometry (LC-MS/MS), and therapy responses were assessed at 3, 6, and 12 months after treatment. Results: Ten patients were included. An extremely high medication adherence for dasatinib was observed; the median medication possession ratio was 99.4%. All 9 CML patients with breakpoints in the major BCR-ABL achieved major molecular response (MMR; major BCR-ABL transcript level below 0.1% on the International Scale) within 12 months, and 5 achieved MMR within 6 months. The receiver operating characteristic curve analysis revealed that the cutoff value for the dasatinib area under the concentration–time curve was 336.1 ng × h/mL (accuracy 88.9%, sensitivity 80.0%, specificity 100%, and receiver operating characteristic curve–area under the concentration–time curve 0.800) for achieving MMR within 6 months. Two patients had interrupted dasatinib treatment because of pleural effusion and diarrhea with intestinal edema, respectively. These edematous adverse events developed after plasma dasatinib Cmin surpassed 3.0 ng/mL. Conclusions: A Medication Event Monitoring System was applied for the direct evaluation of oral dasatinib adherence for the first time, and the clinical effect of dasatinib was investigated under the strict monitoring of patient adherence. Although this study had a small sample size, the plasma concentration monitoring of dasatinib is considered to be useful to predict an earlier molecular response with fewer edematous adverse events. Abstract : Supplemental Digital Content is Available in the Text.